Short Communication: Genetic variation of oceanic manta ray (Mobula birostris) based on mtDNA data in the Savu Sea, Indonesia - MUHAMMAD DANIE AL MALIK; MOCHAMAD IQBAL HERWATA PUTRA; EDY TOPAN; NI PUTU DIAN PERTIWI; ENEX YUNI ARTININGSIH; SILA KARTIKA SARI; SARAH LEWIS; DERTA PRABUNING; ANDRIANUS SEMBIRING (Society for Indonesian Biodiversity, 2022)
Abstract. Malik MDA, Putra MIH, Topan E, Pertiwi NPD, Artiningsih EY, Sari SK, Lewis S, Prabuning D, Sembiring A. 2022. Short Communication: Genetic variation of oceanic manta ray (Mobula birostris) based on mtDNA data in the Savu Sea, Indonesia. Biodiversitas 23: 1700-1706. The Savu Sea, one of Indonesia's top conservation priorities, is home to various marine charismatic species, including the oceanic manta ray (Mobula birostris), whose conservation status is currently endangered and is protected by the Indonesian government. However, due to domestic and global demand for its fishery products, as well as shortcomings in fisheries management, this species is still poached and bycaught in the Savu Sea. Understanding their population structure is important to achieve effective conservation and fisheries management strategies that will have a positive impact on preserving their population in this area. This study aims to reveal the genetic variation of oceanic manta rays in the Savu Sea. Thirty samples from three locations in the Savu Sea were successfully preserved from East Flores (24), West Manggarai (4), and Rote Ndao (2) and then analyzed using ND5 locus from Mithocondiral DNA (mtDNA). The result indicated a close genetic relationship between three locations (East Flores, West Manggarai, and Rote Ndao) based on the phylogenetic tree and Analysis of Molecular Variance (AMOVA) result with value of 0.05158 (P-value = 0.62268) indicated as a single population. In conclusion, the findings of this study provide some insight into the possibility of manta ray populations in the Savu Sea having strong connectivity between areas, which is critical information for regulators and managers to integrate conservation and management strategies within the Savu Sea.